2019
DOI: 10.15203/ciss_2019.012
|View full text |Cite
|
Sign up to set email alerts
|

Changes in motor competence over four decades in 10 to 14-year-old Austrian boys

Abstract: Background: Data on secular trends in motor competence in children and adolescents has been equivocal. While several studies have shown a decline in motor competence over the last several decades there is also research that showed no change or even an increase in motor competence in youth.Methods: Motor competence was assessed via 6 test items in 10- to 14-year-old Austrian boys in the years 1972, 1987 and 2015. At each measurement time participants performed 20m sprint, 800m run, sit ups, jump and reach, one-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
2
1
0
Order By: Relevance
“…The same findings were supported with the latest study by Greier et al [16], who analyzed Tyrolean boys aged 10 to 14 years. Over the measurement time points in 1972 and 2015, endurance declined by 15% [16]. In addition, for Chinese children and adolescents, Bi et al [48] showed a decline between the latest measurement points of 1995 and 2014, and a stagnation from 1985 until 1995.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The same findings were supported with the latest study by Greier et al [16], who analyzed Tyrolean boys aged 10 to 14 years. Over the measurement time points in 1972 and 2015, endurance declined by 15% [16]. In addition, for Chinese children and adolescents, Bi et al [48] showed a decline between the latest measurement points of 1995 and 2014, and a stagnation from 1985 until 1995.…”
Section: Discussionsupporting
confidence: 87%
“…The declining trend is especially obvious in studies with measurement times that are older and with long time periods between follow-ups [42,45,47]. The same findings were supported with the latest study by Greier et al [16], who analyzed Tyrolean boys aged 10 to 14 years. Over the measurement time points in 1972 and 2015, endurance declined by 15% [16].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation